1984
DOI: 10.1111/j.1600-051x.1984.tb01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of probing attachment level measurements

Abstract: The reproducibility of probing attachment level measurements in incisors, cuspids and premolars was studied in 2 groups of patients with severely advanced periodontal disease. The results showed that approximately 90% of the recordings could be reproduced within within +/- 1.0 mm difference. This was found for intra-examiner as well as inter-examiner comparisons of 2 examiners. Measurements using onlay margins for reference point demonstrated somewhat less variability than the use of cemento-enamel junction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
153
2
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(181 citation statements)
references
References 18 publications
21
153
2
5
Order By: Relevance
“…Another factor is operator error such as incorrect angulation of the probe, the amount of pressure applied to the probe, misreading the probe, recording the data imprecisely and miscalculating the attachment loss. 10 The use of constant pressure probes has advantages over the use of manual probe. The constant pressure probe provide a constant probing force which may serve to limit some of the errors associated with probe penetration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor is operator error such as incorrect angulation of the probe, the amount of pressure applied to the probe, misreading the probe, recording the data imprecisely and miscalculating the attachment loss. 10 The use of constant pressure probes has advantages over the use of manual probe. The constant pressure probe provide a constant probing force which may serve to limit some of the errors associated with probe penetration.…”
Section: Discussionmentioning
confidence: 99%
“…The probing itself is the heart of the problem and many improvements have been sought. 10,14,15 The pressure applied at the probe tip is a function of the probing force. Therefore as the probe force increases the CAL measurements also tend to increase.…”
Section: Discussionmentioning
confidence: 99%
“…An onlay-type stent which can guide the probe to an exact location with a proper orientation may be used instead. Clark 1987 and Badersten et al 1984 reported that the onlay-type stent could enhance the reliability of attachment level assessment 13 . Probing depth is defined as the distance from gingival margin to base of the periodontal pocket.…”
Section: Discussionmentioning
confidence: 99%
“…One major difficulty with the "burst" theory of periodontal attachment loss (Goodson et al, 1982;Socransky et al, 1984) is the substantial measurement error of the conventional probes used to produce the underlying data (Rails and Cohen, 1986). Standard deviations reported for measurement of attachment level with conventional probes have ranged from 0.62 to 1.17 (GlavindandLoe, 1967;Badersten et al, 1981Badersten et al, ,1984Goodson et al, 1982;Cercek et al, 1983;Aeppli et al, 1985). Error of this magnitude requires a measured change of 2 to 3 mm in order to conclude safely that change did occur (Haffajee et ah, 1983b).…”
Section: New Clinical Technologiesmentioning
confidence: 99%